Managing Microsoft Teams (MS-700) - Gordon, Adam (Packt Publishing, 2024)
This course is designed for enterprise administrators tasked with evaluating, planning, deploying, and managing Microsoft Teams within their organizations. Beginning with an overview of Microsoft Teams, you will explore its integrated communication and collaboration capabilities. You'll learn how to get started with Teams, including using tools like Network Planner and Network Testing Companion to ensure your network is ready for deployment. As you progress, the course delves into managing teams, including creating and upgrading teams, managing settings and permissions, and using org-wide teams for communication. You will also learn to manage membership, configure dynamic membership, and perform access reviews. The course emphasizes the importance of managing guest access, ensuring secure collaboration with external users through Azure AD and Office 365 Groups. In the advanced sections, you will learn to create and manage policies for messaging, meetings, and live events, as well as configuring audio conferencing and cloud meeting recording. The final sections cover implementing app policies, managing security and compliance, and staying updated with the latest MS-700 exam changes. By the end of the course, you'll be equipped to handle all aspects of Microsoft Teams management in an enterprise environment.